Fire & blood / A Targaryen History # 1 - Martin, George R. R. (New York : Bantam Books, 2018)
The first volume of a definitive two-part history of the Targaryens in Westeros is set centuries before the events of "A Game of Thrones" and answers key questions about the dynasty's origins, conflicts and relationships with dragons.
Keywords: Martin, George R. R; Martin, George R. R